Effects of literature circles on tertiary ESL students' perception and learning of literature - S. Iswarapatham, I. Satkunavathi (2009)
This study seeks to investigate the perception of tertiary ESL literature learners towards literature both before and after their experiences with literature circles. Literature circles are student centered discussion groups that can offer learners an opportunity to develop personal responses to literary texts and to articulate these interpretations in their groups (Kim, 2004). Related studies show that when learners perceive literature in a positive light, they will pick up a literary text and be productively engaged in reading the text for self-fulfillment and not for the sake of finishing an assignment or passing examinations. The main goal of the study is to investigate if learners’ participation in literature circles can help nurture them into thoughtful and probing readers who are able to expand upon their individual interpretations of a literary text and elevate their responses to the text. 50 third year undergraduates majoring in English Literature at the Faculty of Modern Languages and Communication, Universiti Putra Malaysia participated in this study which employed both the quantitative and qualitative techniques of research. Data sources included pre and post experimental questionnaires, observation notes, pre and post tests, audio taped group discussions and interviews, and journals. Findings of this study show that literature circles are able to generate interest among the learners to read and appreciate their literary texts, as well as perceive literature in a more positive light. The results of the study also indicate that learners valued the opportunity to participate in a democratic endeavor that allowed them to voice their own views, as well as listen to other participants’ views. The transactions that occur during literature circles provide opportunities for learners to read, react, express their feelings, and have a sense of control over their learning. The focus is not on extracting information from a text, figuring out the interpretation the teacher wants to hear, or learning about literary elements (Hill, Johnson, & Schlick Noe, 1995: x), but on taking ownership of one’s reading by making predictions, constructing visual images, creating connections to personal experiences and other texts, arguing with the author and evaluating content and writing style (Brabham & Villaume, 2000).